Do more with Less: Improving High Parameter Cytometry Through Overnight Staining. Issue 11 (14th November 2022) - Whyte, Carly E.; Tumes, Damon J.; Liston, Adrian; Burton, Oliver T.
Abstract: Recent advances in flow cytometry have allowed high‐dimensional characterization of biological phenomena, enabling breakthroughs in a multitude of fields. Despite the appreciation of the unique properties of antigens and fluorophores in high‐parameter panel design, staining conditions are often standardized for short surface stains, regardless of antibody affinity or antigen accessibility. Here, we demonstrate how increasing antibody incubation times can lead to substantial improvements in sensitivity, maintaining specificity, and reducing background, while also significantly reducing the costs of high‐parameter cytometry panels. Furthermore, overnight staining reduces the influence of interexperimental variability, assisting accurate pooling over experiments over extended time courses. We provide guidance on how to optimize staining conditions for diverse antigens, including how different fixation strategies can affect epitope accessibility. Overnight staining can thus substantially improve the resolution, repeatability, and cost‐effectiveness of high‐parameter cytometry. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC.